Association between cerebrovasoreactivity and stroke in cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy - Mukai, Mao; Hamano, Ai; Mizuta, Ikuko; Yokota, Isao; Watanabe-Hosomi, Akiko; Matsuura, Hiraku; Koizumi, Takashi; Matsuura, Jun; Ohara, Tomoyuki; Matsushima, Shigenori; Teramukai, Satoshi; Yamada, Kei; et al. (Frontiers in Neurology, 2023)
Background: Impaired cerebrovasoreactivity is thought to play an important role in the pathophysiology of cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL). We aimed to clarify the association between cerebrovascular reactivity and stroke in patients with CADASIL. Methods: We retrospectively recruited 14 patients with CADASIL, eight of whom had symptomatic stroke. They underwent quantitative single-photon emission computed tomography using an autoradiographic method at rest and after acetazolamide (ACZ) administration. Regional cerebral blood flow (rCBF) in the cerebral cortex, lenticular nucleus, thalamus, and cerebellum was measured. We compared the rCBF parameters between patients with and without stroke. Results: The baseline characteristics and magnetic resonance imaging findings were similar between the two groups, except for a higher frequency of pyramidal tract sign (75% versus 0%) and a larger number of old lacunes (15.4 ± 8.8 versus 2.2 ± 1.8) in the patients with stroke. Of the rCBF parameters measured, significantly lower flow (mL/100 g/min) was observed in ACZ-rCBF in the thalamus (35.6 ± 9.4 versus 51.1 ± 7.6, p = 0.01) and ΔrCBF in the thalamus (10.6 ± 3.7 versus 21.0 ± 7.9, p = 0.02) in the patients with stroke. Conclusion: Cerebrovasoreactivity in the thalamus was significantly associated with stroke in patients with CADASIL.